Using Anderson's Model of Health Service Utilization to Assess the Use of HIV Testing Services by Sexually Active Men in Ghana - Seidu, Abdul-Aziz (Frontiers in Public Health, 2020)
Introduction: Globally, HIV testing and counseling is considered a key cost-effective component of HIV prevention and treatment. This study sought to use Anderson's model of health service utilization to assess the uptake of HIV testing services by sexually active men in Ghana. Materials and Methods: Data were from the 2014 Ghana Demographic and Health Survey. Both bivariate and multivariate analysis were conducted. The multivariate analysis results are presented as Adjusted Odds ratios (AORs) with 95% confidence intervals (CI). Statistical significance was declared at p < 0.05. Results: A total of 3,052 sexually active men aged 15–59 were included in the analysis. Of these, 25.4% tested for their HIV status. Men aged 30–39 (AOR = 2.715, CI = 1.458, 5.054), those with higher level of education (AOR = 3.566,CI = 2.309, 5.509), married (AOR = 1.50, CI = 1.167, 1.931), and men in Upper East (AOR = 2.625, CI = 1.608, 4.285) had higher odds of HIV testing uptake than their counter parts aged 15–19, those with no formal education unmarried and those in Western Region, respectively. However, men with no religion (AOR = 0.606, CI = 0.376, 0.975) and those who belong to the Mole-Dagbani ethnic group (AOR = 0.633, CI = 0.429, 0.934) had lower odds of HIV testing uptake compared to those who are Christians, and Akans, respectively. Men who have subscribed to health insurance (AOR = 1.896, 95% CI = 1.361, 2.643), those in the rich wealth quintile (AOR = 1.896, CI = 1.361, 2.643), those who read newspaper (AOR = 1.552, CI = 1.198, 2.012), listened to radio (AOR = 1.530, CI = 1.087, 2.153) at least once a week, and men who experienced discharge from their penis (AOR = 1.056, CI = 1.200, 1.515) had higher odds of HIV testing uptake. Conclusion: Uptake of HIV testing among Ghanaian men is relatively low. There is the need for a concerted effort by various stakeholders to strengthen current efforts to target younger and unmarried men, men with low level of education, those who do not profess any religious affiliation and men belonging to Mole-Dagbani ethnic group.